Mechanisms and treatments for shoulder injuries in overhead throwing athletes - Zaremski, J. L.; Wasser, J. G.; Vincent, H. K. (Current Sports Medicine Reports, 2017)
Shoulder injuries in overhead throwing athletes are very common. Throwing volume and mechanical forces that are placed on the glenohumeral joint and associated soft tissue structures are contributors. Poor biomechanics and weak links in the kinetic chain place this athletic population at increased risk for shoulder injuries. Common biomechanical deficiencies in overhead throwing athletes typically involve poor sequential timing of muscle activity and insufficient coordination also presented in shoulder elevation and other functional tasks. Kinetic chain deficits will lead to injury due to poor transference of energy from the lower extremities to the dominant upper extremity. Correction of these deficits involves effective treatment and prevention strategies. These include core and hip strengthening, balance training, optimize timing of biomechanical phases and events for each throwing movement, and following recommended rest guidelines. This article will synopsize current evidence of sport-specific injury mechanisms, injury treatment, and prevention of the shoulder in overhead throwing athletes.